Skład i zasady funkcjonowania rządu Królestwa Szwecji: [Composition and principles of functioning of the government of the Swedish Kingdom] (Studia Prawnicze / The Legal Studies, 1981)
Present structure of the Swedish government is derived from the structure ,of State Council determined by the Act of 1.809 or the Form of Government. Evolution of the government from a body composed of advisors and assistants attached to the monarch was directed towards the emancipation of that organ from the influence of the king and strengthening of its ties with the parlament and political parties represented in Riksdag. Final sealing of the dependency between the political composition of the government and that of the Riksdag took place in 1917. These processes deepened the distance between formal way in which the constitution treats the governments a group of king's advisors, and the reality in which the government was !gaining more and more independence as a state organ.New Act of 1974 on the Form of Government completely moved away from the former formula, shifting the whole of executive power on the government, ministers, and central and local organs of administration subjected to the cabinet. On the other hand, the principle of particular dualism of executive organs with all-national scope of activity was still kept in force. It constists in separating central organs of administration independent of the ministers and chiefs of departments (or helping ministers) and subjecting them to the government i n g r e m i o. Also, the role of the prime minister combining the attributes of a leader of a governing party with customarily constant position of a head of the government, has increased especially during the period of lasting domination of the social-democrats (1932-1976).New Swedish Constitution of 1974 consolidated the position of the head of the cabinet ensuring him - among other rights - the right to nominate remaining members of the cabinet. Also, some elements of procedure of making a decision by the government were regulated. However, regulation of the principles of functioning of a cabinet still remain only fragmentary.